Cuestionamientos al modelo extractivista neoliberal desde el Sur Capitalismo, territorios y resistencias - Alister, Cristian; Cuadra, Ximena; Julián-Vejar, Dasten; Pantel, Blaise; Ponce, Camila (Ariadna Ediciones, 2021)
This book is part of the desire to nurture an interdisciplinary dialogue between multiple social, cultural and territorial spheres in relation to extractivism, its study and experience. The book is an instrument that expresses an intertwining between actors, networks and territorial realities that shape the wealth and diversity of the territories currently threatened by extractivism. Allowing a reflection on the present and the future of the current development model, this publication integrates various types of texts and writings to construct a material that is both information and analysis, but also as a dissemination material on the multiple dimensions and facets of extractivism in the south. The idea consists of being able to make multiple languages and forms of interpretation of reality coexist that account for the different senses of local experience in the face of extractivism.